2021
DOI: 10.1093/hmg/ddab279
|View full text |Cite
|
Sign up to set email alerts
|

Meta-GWAS of PCSK9 levels detects two novel loci atAPOBandTM6SF2

Abstract: Background Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a key player in lipid metabolism, as it degrades LDL receptors from hepatic cell membranes. So far, only variants of the PCSK9 gene locus were found to be associated with PCSK9 levels. Here we aimed to identify novel genetic loci that regulate PCSK9 levels and how they relate to other lipid traits. Additionally, we investigated to what extend the causal effect of PCSK9 on coronary artery disease (CAD) is mediated by LDL-C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 78 publications
5
15
0
Order By: Relevance
“…For stroke, we found significant causal associations with increased risk of large artery ischaemic stroke subtype (MRlog(IS-LA OR)=0.27, p=0.011). Whilst genetic PCSK9 effects on LDL, total cholesterol and CHD have been found previously 36,75 , effects of PCSK9 on HDL cholesterol and large artery ischaemic stroke have not been substantiated by previous MR studies, likely due to decreased power. These findings extends the corroborated effects observed across multiple randomised clinical trials of PCSK9 inhibitors 72 .…”
Section: Pcsk9 Pqtls Reflect Pharmacological Effects On Cholesterol A...mentioning
confidence: 87%
“…For stroke, we found significant causal associations with increased risk of large artery ischaemic stroke subtype (MRlog(IS-LA OR)=0.27, p=0.011). Whilst genetic PCSK9 effects on LDL, total cholesterol and CHD have been found previously 36,75 , effects of PCSK9 on HDL cholesterol and large artery ischaemic stroke have not been substantiated by previous MR studies, likely due to decreased power. These findings extends the corroborated effects observed across multiple randomised clinical trials of PCSK9 inhibitors 72 .…”
Section: Pcsk9 Pqtls Reflect Pharmacological Effects On Cholesterol A...mentioning
confidence: 87%
“…In the present study, we genotyped polymorphisms of four SNPs in the PCSK9 gene and found that rs2483205 and rs2495477 were associated with T2DM. Rs2495477 is located in the fifth intron of the PCSK9 gene and affects the splicing process of RNA, which may lead to reduced PCSK9 mRNA levels [ 39 ]. Rs2483205 is also located in the intronic region of the PCSK9 gene and regulates the promoter flanking regions.…”
Section: Discussionmentioning
confidence: 99%
“… 49 We clumped SNPs at linkage disequilibrium R 2 =0.001, leaving 6 independent SNPs comprising the LDL‐C–based PCSK9 instrument. Because only 3 of the 6 independent PCSK9 variants in the LDL‐C instrument were found in the PCSK9 protein level data, 50 we also created a PCSK9–LDL‐C instrument comprising only variants associated with both LDL‐C ( P <5×10 −8 ) and PCSK9 protein levels ( P <5×10 −6 ), 50 as a biologically conservative instrument and sensitivity analysis to assess the MR exclusion restriction assumption. We included an LDL‐C–based PCSK9 instrument with 3 independent SNPs derived from the earlier 2013 GLGC GWAS of circulating LDL‐C levels (N≤173 082) as an additional sensitivity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Next, because instrumentation of PCSK9 in LDL‐C does not measure changes in PCSK9 levels directly, and because current anti‐PCSK9 monoclonal antibodies target the PCSK9 protein, 44 we supplemented the PCSK9 instrument derived from LDL‐C data with SNPs associated with circulating PCSK9 protein levels using protein quantitative loci (pQTL) data from 10 186 individuals of European ancestry. 50 We extracted and clumped SNPs as above, leaving 2 independent SNPs within the PCSK9 locus. PCSK9 protein levels were measured in normalized protein units.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation